Participant Reflexivity in Organizational Research Design. (October 2020) - Cassell, Catherine; Radcliffe, Laura; Malik, Fatima
Despite the considerable interest in researcher reflexivity within the organizational literature, little attention has been paid to participant reflexivity, here defined as the reflexive considerations of research participants that are stimulated by their involvement in research. Our argument is that engagement in the research process is a context where such reflexive thinking is likely to happen and that through certain methodological approaches, participants' reflexive thinking becomes more conscious and therefore potentially accessible to the researcher. In identifying the participant reflexivity that emerged as part of a photo-elicitation study of work-life balance and conflict, we outline the kinds of reflexive dialogue that participants reported as being stimulated by involvement in the research and explore the link between emotion and reflexive practice. Hence our paper contributes to our understanding of qualitative research and reflexivity first by highlighting empirically the kinds of internal dialogue reported when participants engage in self-reflexivity as part of the research process; second, by outlining how we can access participant reflexivity methodologically, including through emotions; and third, by explicating the value for researchers in accessing participant reflexivity.